Seasonal, lunar and tidal control of ichthyoplankton dynamics at the interface between a temperate estuary and adjacent coastal waters (western Portugal) - Lígia Primo, Ana; Miranda Azeiteiro, Ulisses; Cotrim Marques, Sónia; Ré, Pedro; Ângelo Pardal, Miguel (Scientia Marina, 2012)
Influence of season, lunar-tide cycle and tide on ichthyoplankton at the interface between Mondego estuary and the adjacent coast and on up-estuary transport was evaluated. Seasonal samples were collected at a fixed station at the mouth of the estuary during diel cycles, at neap and spring tides. Additionally, four sampling stations along the estuary were assessed. Pomatoschistus spp. was the main estuarine taxon, while Sardina pilchardus and Parablennius pilicornis were the most important marine species. Ichthyoplankton entrance and transport along the estuary presented a seasonal pattern with higher densities during summer. Lunar-tide cycle also represented an important influence, structuring communities that reach the estuary and their subsequent distribution. Solea senegalensis and Sardina pilchardus seemed to take advantage of spring tides to enter the estuary. S. pilchardus appear to be using tides to move upstream of the estuary. Ichthyoplankton entrance in the estuary seemed related to species spawning period, while its distribution within the estuary depends on in situ spawning and on the capacity of species to counteract currents and river flow. The present study provides a better understanding of ichthyoplankton dynamics at the interface of two coastal systems, reinforcing knowledge of the lunar-tide cycle influence on ichthyoplankton communities.